Surface Waves in Fluid-saturated Porous Layer Bounded by A Liquid Layer and An Orthotropic Elastic Half Space - Pal, P. C.; Mandal, Dinbandhu (Journal of Informatics and Mathematical Sciences, 2012)
The dispersion equation of surface waves is studied in a fluid saturated porous layer occupying an orthotropic elastic half space and lying under the uniform liquid layer. The frequency equation is obtained as determinant of order ten. Some special cases are derived. Numerical results are obtained for two different cases and are shown by graphs.